The opportunities for use the peer land exchange during land management in Ukraine - Malashevskyi, Mykola; Palamar, Alena; Malanchuk, Mariia; Bugaienko, Olena; Tarnopolsky, Evgen (Geodesy and Cartography, 2018)
The preconditions and general directions of inter economic land surveying in the modern conditions of Ukrainian in accordance to the perspectives of peer land exchange implementation have been analyzed. The measures, implementation of which is advisable based on peer land exchange as the key mechanism have been singled out and substantiated. According to the current legislation of Ukraine, the main types of documentation for land management, which may provide the peer land exchange are defined. Land exchange is a common way of streamlining existing land ownership and land use in domestic and foreign practice. In particular, an equivalent exchange is often aimed at regrouping a significant amount of land use in order to optimize their structure. At the present time, the coordination of the interests of landowners in the process of optimizing the multitude of land uses of settlements is of particular relevance. For example, there is a need to locate facilities that have environmental and social significance, improvement and changing boundaries of land management objects at different levels. In the context of certain tasks, given the legally defined issue of exchange agreements concluding, the settlement of the land exchange process requires a technical justification.